Acquisition of Involuntary Spinal Locomotion (Spinal Walking) in Dogs with Irreversible Thoracolumbar Spinal Cord Lesion: 81 Dogs. (26th February 2017) - Gallucci, A.; Dragone, L.; Menchetti, M.; Gagliardo, T.; Pietra, M.; Cardinali, M.; Gandini, G.
Abstract : Background: Spinal walking (SW) is described as the acquisition of an involuntary motor function in paraplegic dogs and cats without pain perception affected by a thoracolumbar lesion. Whereas spinal locomotion is well described in cats that underwent training trials after experimental spinal cord resection, less consistent information is available for dogs. Hypothesis: Paraplegic dogs affected by a thoracolumbar complete spinal cord lesion undergoing intensive physical rehabilitation could acquire an autonomous SW gait under field conditions. Animals: Eighty‐one acute paraplegic thoracolumbar dogs without pelvic limb pain perception. Methods: Retrospective study of medical records of dogs selected for intensive rehabilitation treatment in paraplegic dogs with absence of pain perception on admission and during the whole treatment. Binary regression and multivariate logistic regression were used to analyze potential associations with the development of SW. Results: Autonomous SW was achieved in 48 dogs (59%). Median time to achieve SW was of 75.5 days (range: 16–350 days). On univariate analysis, SW gait was associated with younger age ( P = .002) and early start of physiotherapy ( P = .024). Multivariate logistic regression showed that younger age (≤60 months) and lightweight (≤7.8 kg) were positively associated with development of SW ( P = .012 and P < .001, respectively). BCS, full‐time hospitalization, and type and site of the lesion were not significantly associated with development of SW. Conclusions: Dogs with irreversible thoracolumbar lesion undergoing intensive physiotherapic treatment can acquire SW. Younger age and lightweight are positively associated with the development of SW gait.